RANCANG BANGUN APLIKASI PENJUALAN PULSA ELEKTRIK BERBASIS JAVA J2SE (Information Technology and Telematics, 2012)
Nowadays mobile phones are a common item to most people seemed to be a mandatory item to have. Along with the growth of mobile phone usage, the growing use of credit is also directly proportional to it. This raises the promising business opportunities and prospects for long. But in the general method are still many shortcomings on doing top-up transaction such as recording transactions are still done by writing in the book, typing specified sms format for provider by manual on mobile phones. Starting from that several shortcomings, so writer take the title of the final project is “Design and Development Electronic Voucher Top-Up Java J2SE Based”. Using a computerized media, where to make a sales transaction, seller only do insert data to application and the application automatically send a specified sms format to a provider, and application will record all of the sales transaction to the sales database. That’s expected to change the sales process become easier, practical ad effective. Keywords : electronic voucher, top up, provider, mobile phone